Electrophoretic deposition and sintering of a nanostructured manganese–cobalt spinel coating for solid oxide fuel cell interconnects. Issue 6 (1st May 2016) - Mirzaei, M.; Simchi, A.; Faghihi-Sani, M.A.; Yazdanyar, A.
Abstract : Solid oxide fuel cell (SOFC) is one of the promising candidates for clean energy production. Due to the high operating temperature of SOFCs, a protective coating is commonly applied on the surface of interconnects to prevent oxidation. In this study, electrophoretic deposition was employed to prepare a manganese–cobalt spinel coating on ferritic stainless steel (AISISAE430) substrates. Nanostructured MnCo2 O4 powder with an average crystallite size of 60 nm was utilized and the sintering behavior of the coatings at different temperatures was studied. Non-isothermal and isothermal sintering behavior of the powder were examined by employing a sensitive dilatometer. Master sintering curve of the spinel powder was also established. The activation energy of sintering was determined to be 513±13 kJ mol −1 . Finally, the oxidation behavior and electrical properties of the prepared specimens were studied. Improved oxidation resistance and better electrical conductivity of the stainless steel substrate were attained in the presence of electrophoretic deposited MnCo2 O4 coating.